Physiological and agronomic characterization of post-flowering heat stress in winter wheat - Bergkamp, Blake Leo (Kansas State University, 2017)
Post-flowering heat stress is one of the major environmental constraints for wheat (Triticum aestivum L.) production in the state of Kansas, where wheat is the most widely grown grain crop. Studies have shown that the optimal temperature for wheat grain development is approximately 21°C. During the grain filling stage for wheat in Kansas, it is fairly common for temperatures to reach more than 30°C and above. These scenarios have resulted in lower productivity and yield in Kansas compared to other regions of the United States. Therefore the objectives of this research project included: phenotyping seven Kansas varieties for post-flowering heat tolerance in a controlled environment growth chamber study as well as in two field experiments, estimation of spike and flag leaf senescence in wheat exposed to post-flowering heat stress, and identifying potential genetic donors for heat tolerance from winter wheat breeding lines and Near Isogenic Lines developed from Kansas State University’s Wheat Breeding Program. To impose heat stress in the controlled growth chambers, plants grown at 25°C were transferred to high day temperature (35°C) chambers ten days after the first sign of anthesis. Under field conditions, custom built “heat tents” were placed over the wheat plots ten days after first flowering and remained until maturity. Plants grown under heat stress exhibited early senescence, indicating a shorter grain filling period compared to the controls. Early-maturing varieties recorded greater percent reductions in grain yield under heat stress. Post-flowering heat stress induced significant reductions in thousand kernel weight, grain number, harvest index, and grain yield. Spike and flag leaves effective quantum yield of PSII was reduced more drastically under growth chamber stress exposure compared to field grown plants. Significant genetic variation in the spike and flag leaf senescence initiation and the differential rate of senescence among the seven tested varieties suggested the potential for considering this trait in breeding programs. Compared to the commercially relevant varieties, breeding lines varied less under heat stress with a few lines recording a greater degree of heat resilience and experienced little to no drop off in heat stress conditions compared to control. The reduced performance under heat stress for the seven varieties highlights the genuine need to explore wider genetic diversity, including wild wheat, to infuse greater resilience into ongoing wheat breeding programs. However, the results observed in the breeding lines indicate that introducing larger genetic diversity may aid in developing greater heat stress resilient wheat varieties for current and future changing climate.
Keywords: Agronomy; Wheat; Physiology; Heat Stress